Vertical And Horizontal Distribution Of Zinc In Soils Overlying The Flat Gap Mine, Tennessee - Alan D. Hoagland (Society for Mining, Metallurgy & Exploration, 1962)
The Flat Gap Mine is on Copper Ridge in the Appalachian Valley of East Tennessee, Large zinc orebodies occupy zones of solution and collapse breccias in lower Ordovician Kingsport limestone and dolomite, The principal ore mineral is sphalerite and the principal gangue is dolomite, The orebearing horizons are considerably more than 95% covered by thick residual clay, and geochemical prospecting under these conditions is an effective exploration technique which played an important role in the discovery and exploration of the Flat Gap Mine, The residual nature of the over-burden at Flat Gap is emphasized, Background heavy metals (mainly zinc) range from 50 to 200 ppm, and the anomalies range to 3000 ppm and more, About 80% to 9W0 of the soil zinc is in relatively insoluble form in solid solution with the hydrous iron oxides and in the crystal lattice of the clay minerals. Quite discrete zones in the soil with sharply contrasting metal value boundaries mark vestiges of bedrock mineralization, and such anomalous soil areas are often contiguous with partially weathered ore. It has not been possible on the basis of chemical criteria to distinguish between an anomaly formed from non-commercial mineralization and one formed from ore.